English teaching in distant education policy development: Ukrainian aspect - Paziura, Nataliia V.; Kodalashvili, Oksana B.; Bozhok, Oleksandra S.; Romaniuk, Viktoriia L.; Zlatnikov, Valentyn H. (Linguistics and Culture Review, 2021)
The problem of distance learning in practice arose in Ukraine over the last period, when quarantine measures were introduced due to the spread of COVID-19. After the announcement by the government and the relevant state institutions of compulsory distance learning, teachers faced real problems in the implementation of this form of education, which require urgent consideration and resolution. And although distance learning has become an integral part of the daily life of most students during quarantine, it does not meet the requirements of the modern information society. These facts explain the relevance of this study. The purpose of this paper is to analyse and generalise the present state of distance learning in Ukraine in general and in terms of language study, including English. The present state of distance learning in Ukraine and the prospects for its development are determined using theoretical analysis, synthesis, comparison, individualisation and generalisation. Distance learning can be a powerful tool for everyone who wants to learn foreign languages and an effective means of expanding the creative potential of students.